Taxonomic study of morphology and distribution of Nannophya pygmaea Rambur, 1842 (Odonata: Libellulidae) with a discussion on the possibility of cryptic diversity and larval comparison of genera in subfamily Brachydiplacinae - Nguyen, Minh Ty; Novelo-Gutiérrez, Rodolfo; Ngiam, Robin W. J.; Kim, Junggon; Phan, Quoc Toan; Keetapithchayakul, Tosaphol Saetung (Zootaxa, 2026)
A description of the adult and last instar larva of Nannophya pygmaea Rambur, 1842 is presented, based on reared material from Vietnam and additional specimens obtained from Peninsular Malaysia and Singapore. Adult morphology of both sexes is documented to ensure accurate species confirmation and to demonstrate consistency with previously established diagnostic characters. Updated distributional data for Nannophya Rambur, 1842 in Asia are synthesized from verified field records, curated online biodiversity repositories (GBIF and iNaturalist), and published literature. Diagnostic comparisons of N. pygmaea with N. koreana Bae, 2020 as well as with other members of Brachydiplacine are provided. The taxonomic status and distribution of N. pygmaea are discussed. The essential baseline data for future systematic, biogeographic, and conservation studies are provided.